Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/su15118554
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Organic Food Consumption in Narrowing the Green Gap

Abstract: Understanding and recognising environmentally-friendly behaviour are vital in achieving the Sustainability Development Goals and driving the economy for countries and producers of environmentally-friendly goods. Nevertheless, various stakeholders have expressed concern about the existing green gap, which greatly hinders their marketing efforts. This situation persists as mainstream research investigates people’s purchasing intentions, under the notion that the intention to perform a specific behaviour would ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…This can include developing new tourism products and services that appeal to a broader range of travellers and investing in sustainable practices to reduce environmental impact and improve social responsibility. By adopting these strategies, tourism businesses can increase their appeal to Muslim travellers while also enhancing their competitive advantage and pursuing sustainable growth for the long term (Chekima et al , 2023; Nicole et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This can include developing new tourism products and services that appeal to a broader range of travellers and investing in sustainable practices to reduce environmental impact and improve social responsibility. By adopting these strategies, tourism businesses can increase their appeal to Muslim travellers while also enhancing their competitive advantage and pursuing sustainable growth for the long term (Chekima et al , 2023; Nicole et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient data pertaining to the UAE, a socially and economically unique Middle Eastern nation, remains evident. A comprehensive review of research on FinTech has revealed a consensus among scholars about the importance of facilitating conditions in influencing individuals' behavioural intention (Bin-Nashwan, 2022; Rahim et al, 2022;Yeh et al, 2022;Chekima et al, 2023). This implies that by providing ample supporting resources, such as expertise in technology, convenient internet connection, appropriate smart devices, expert coaching and assistance, consumers can cultivate favourable impressions and achieve a smooth user experience on the FinTech platform.…”
Section: Facilitating Conditionsmentioning
confidence: 99%
“…This study focuses on the youth in an Eastern context where the increasing problem of bankruptcy is alarming. This study also attempts to close the gap by introducing future orientation as a moderator by adopting and extending the theory of planned behavior (TPB), as suggested by Chekima et al (2023). Ajzen (2015) of time value, or our sense of time, as a moderator in the individual decision making process.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%